Stress Coping Strategies in Hemodialysis and Kidney Transplant Patients - GÜRKAN, AYSEL (ELSEVIER SCIENCE INC, 2015)
Objective. The aim of this study was to determine the levels of anxiety and depression, and stress coping strategies used by hemodialysis and kidney transplant patients. Methods. This study included 138 hemodialysis patients treated at the two private dialysis centers and 76 kidney transplantation patients followed up at the private hospital. Data were collected with socio-demographic characteristics, the Hospital Anxiety and Depression Scale, and the Coping Strategies Questionnaire (COPE). Results. The anxiety and depression scores were significantly lower among the transplant group versus the hemodialysis patients. The use of non-functional coping strategies was higher among the patients who were treated with hemodialysis, compared to the renal transplantation patients. The use of problem focused and emotional focused coping strategies were higher among the renal transplant patients, compared to hemodialysis patients. When all participants were evaluated together, turning to religion was the most frequent coping strategy followed by active coping, and positive reinterpretation. In hemodialysis patients, there was a significantly negative correlation between age and problem-focused, emotion-focused and non-functional coping strategies. In contrast, the correlation between education level and both problem-focused and emotion-focused coping strategies was significantly positive. In transplant patients, gender and education level were significantly negative correlated with emotion-focused coping strategies. Conclusion. The results of data analysis showed that the hemodialysis patients used fewer functional coping strategies and had more anxiety and depression than kidney transplant patients. It would be helpful to know an individual's coping strategies in the case of a stressful situation in order to determine treatment goals and monitor therapeutic efficacy.
Keywords: QUALITY-OF-LIFE; AMBULATORY PERITONEAL-DIALYSIS; DEPRESSION; ANXIETY; RECIPIENTS; DISEASE